Terahertz range quantum well infrared photodetector - Graf, Marcel; Scalari, Giacomo; Hofstetter, Daniel; Faist, Jérôme; Beere, Harvey; Linfield, Edmund; Ritchie, David; Davies, Giles (My University, 2004)
We demonstrated a GaAs/AlGaAs-based far-infrared quantum well infrared photodetector at a wavelength of λ=84 µm. The relevant intersubband transition is slightly diagonal with a dipole matrix element of 3.0 nm. At 10 K, a responsivity of 8.6 mA/W and a detectivity of 5×107 cm √Hz/W have been achieved; and successful detection up to a device temperature of 50 K has been observed. Being designed for zero bias operation, this device profits from a relatively low dark current and a good noise behavior.